17, β‐estradiol inhibits hepatitis C virus mainly by interference with the release phase of its life cycle. (25th November 2016) - Magri, Andrea; Barbaglia, Matteo N.; Foglia, Chiara Z.; Boccato, Elisa; Burlone, Michela E.; Cole, Sarah; Giarda, Paola; Grossini, Elena; Patel, Arvind H.; Minisini, Rosalba; Pirisi, Mario
Abstract: Background & Aims: Oestrogen and oestrogen‐mediated signalling protect from hepatitis C virus through incompletely understood mechanisms. We aimed to ascertain which phase(s) of hepatitis C virus life cycle is/are affected by oestrogens. Methods: Huh7 cells infected with the JFH1 virus (genotype 2a) were exposed to dehydroepiandrosterone, testosterone, progesterone and 17β‐estradiol (tested with/without its receptor antagonist fulvestrant). Dose–response curves were established to calculate half maximal inhibitory concentration values. To dissect how 17β‐estradiol interferes with phases of hepatitis C virus life cycle, its effects were measured on the hepatitis C virus pseudo‐particle system (viral entry), the subgenomic replicon N17/JFH1 and the replicon cell line Huh7‐J17 (viral replication). Finally, in a dual‐step infection model, infectious supernatants, collected from infected cells exposed to hormones, were used to infect naïve cells. Results: Progesterone and testosterone showed no inhibitory effect on hepatitis C virus; dehydroepiandrosterone was only mildly inhibitory. In contrast, 17β‐estradiol inhibited infection by 64%‐67% (IC50 values 140‐160 nmol/L). Fulvestrant reverted the inhibition by 17β‐estradiol in a dose‐dependent manner. 17β‐estradiol exerted only a slight inhibition (<20%) on hepatitis C virus pseudo‐particles, and had no effect on cells either transiently or stably (Huh7‐J17 cells) expressing the N17/JFH1 replicon. In the dual‐step infection model, a significant half maximal inhibitory concentration decline occurred between primary (134 nmol/L) and secondary (100 nmol/L) infections ( P =.02), with extracellular hepatitis C virus RNA and infectivity being reduced to a higher degree in comparison to its intracellular counterpart. Conclusions: 17β‐estradiol inhibits hepatitis C virus acting through its intracellular receptors, mainly interfering with late phases (assembly/release) of the hepatitis C virus life cycle.